2022
DOI: 10.3390/math10203910
|View full text |Cite
|
Sign up to set email alerts
|

Multifractal Characteristics on Temporal Maximum of Air Pollution Series

Abstract: Presenting and describing a temporal series of air pollution data with longer time lengths provides more concise information and is, in fact, one of the simplest techniques of data reduction in a time series. However, this process can result in the loss of important information related to data features. Thus, the purpose of this study is to determine the type of data characteristics that might be lost when describing data with different time lengths corresponding to a process of data reduction. In parallel, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Furthermore, flexible multivariate modeling via the copula approach was also used to examine the dynamic dependence structure between PM 10 and other air pollutants [23]. Using a multifractal technique on API in Klang, Masseran [24] showed that hourly API data contains the most information on air pollution and that the data reduction process is affected by the data duration. Moreover, survey data obtained from the cross-sectional survey is used to study Malaysians' awareness of air pollution and its related impacts on human health, where the surveys pointed out the need to increase the awareness of air pollution among Malaysian [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, flexible multivariate modeling via the copula approach was also used to examine the dynamic dependence structure between PM 10 and other air pollutants [23]. Using a multifractal technique on API in Klang, Masseran [24] showed that hourly API data contains the most information on air pollution and that the data reduction process is affected by the data duration. Moreover, survey data obtained from the cross-sectional survey is used to study Malaysians' awareness of air pollution and its related impacts on human health, where the surveys pointed out the need to increase the awareness of air pollution among Malaysian [25,26].…”
Section: Introductionmentioning
confidence: 99%